Stereotactic Radiation for the Comprehensive Treatment of Oligometastases (SABR-COMET): Extended Long-Term Outcomes - Harrow, Stephen; Palma, David A.; Olson, Robert; Gaede, Stewart; Louie, Alexander V.; Haasbeek, Cornelis; Mulroy, Liam; Lock, Michael; Rodrigues, George B.; Yaremko, Brian P.; Schellenberg, Devin; Ahmad, Belal; et al. (International journal of radiation oncology, biology, physics, 2022)
Long-term randomized data assessing the effect of ablative therapies in patients with oligometastases are lacking. The Stereotactic Ablative Radiotherapy for the Comprehensive Treatment of Oligometastases (SABR-COMET) randomized phase 2 trial was originally designed with 5 years of follow-up, but the trial was amended in 2016 to extend follow-up to 10 years. Herein we report oncologic outcomes beyond 5 years. Patients were eligible if they had a controlled primary tumor and 1 to 5 metastases, with all metastases amenable to SABR. Patients were randomized in a 1:2 ratio between palliative standard-of-care treatment (control arm) versus SABR to all metastases plus standard of care (SABR arm). The primary endpoint was overall survival (OS) and secondary endpoints included progression-free survival (PFS), toxicity, quality of life (using the Functional Assessment of Cancer Therapy: General [FACT-G]), and time to new metastases. Ninety-nine patients were randomized between 2012 and 2016 (n = 33 in arm 1 vs n = 66 in arm 2). Primary tumor sites included lung (n = 18), breast (n = 18), colon (n = 18), prostate (n = 16), and other (n = 29). Eight-year OS was 27.2% in the SABR arm versus 13.6% in the control arm (hazard ratio, 0.50; 95% confidence interval, 0.30-0.84; P = .008). Eight-year PFS estimates were 21.3% versus 0.0%, respectively (hazard ratio, 0.45; 95% confidence interval, 0.28-0.72; P < .001). Rates of grade ≥ 2 acute or late toxic effects were 30.3% versus 9.1% (P = .019), with no new grade 3 to 5 toxic effects. FACT-G quality of life scores declined over time in both arms, but there were no differences in quality of life scores between arms. The use of systemic therapy overall was similar between arms, but patients in the SABR arm were less likely to require cytotoxic chemotherapy (33.3% vs 54.6%, respectively, P = .043). SABR achieved durable improvements in OS and PFS, with no new major toxicity signals with extended follow-up. A minority of patients randomized to the SABR arm (21.3%) achieved > 5 years of survival without recurrence.